Perspectivas contemporâneas dos direitos autorais: uma saída para os conflitos (inter)nacionais - Leal Galante, Melina (2014)
Copyright has functions as the promotion and safeguarding of intellectual production in favor of the plaintiff and society, the result of creative and original manifestation, ensuring the creator a monopoly of his work and balancing the interests of its use by third parties. The objective is to demonstrate the applicability of an international mechanism for protection of copyright from the flexibility of systems, the latter were a third way.